CALCULATION OF INSURANCE RISK AND TOTAL DIVIDEND EXPECTATIONS USING RECURSIVE METHOD - Dwinita Purvitasari, Sylvia
In actuarial science, the concept of ruin theory is the main focus for assessing the risk bankruptcy for an insurance or financial company due to improper management of funds. One model that can be used to analyze ruin is the Sparre Andersen risk model approach, which depends on discrete time. This model incorporates several threshold levels that constitute the insurance company’s minimum surplus requirements, external financial activities, and dividend payments. Apart from that, risk analysis can also be used to estimate the amount of dividends as the profit received by the company before reaching ruin. In this research, construction is carried out to calculate the probability of a ruin occurring and the expected total dividends before a ruin occurs recursively by utilizing large surpluses over time. From the numerical results of the calculations, the chance of ruin will be smaller if the maximum debt value is obtained, while the expected total dividend before the ruin occurs can be increased by increasing the maximum value of debt, reducing the surplus limit for dividend payments, and increasing constant dividend payments.